Tinjauan Hukum Islam terhadap Hak-Hak Pekerja Bengkel X di Belitung Timur - Ikrima Azkury Nabella; Popon Srisusilawati; Akhmad Yusup (UNISBA Press, 2024)
Abstract. Labor and employment issues continue to receive the attention of many groups, including work agreements, working time, inadequate wages and health insurance. Such as the issue of wages and working time that occurred at Workshop